SOIL-ARCHAEOLOGICAL STUDIES OF THE EARLY BRONZE AGE SETTLEMENT ARTANISH-9 (REPUBLIC OF ARMENIA) - Homutova, Tat'ana Eduardovna; Cernyseva, Elena Vladislavovna; Potapova, Anastasia Vladimirovna; El'cov, Maksim Vital'evic; Pinskoj, Viktor Nikolaevic; Amiran, Mariam Armenovna (History, Archeology and Ethnography of the Caucasus, 2023)
The article presents the results of comprehensive soil and archaeological studies of the early Bronze Age settlement of the Kura-Araks culture Artanish-9, located on the shore of Lake Sevan (Republic of Armenia). The cultural layer inside the residential building and in the inter-residential space is investigated. A microelement analysis of the cultural layer was carried out. To assess the intensity of transformation of the original soil as a result of the vital activity of ancient population, the coefficients of "anthropogenic input" are proposed, which reflect the intensity of the input of anthropogenic material into the soil and are calculated as the ratio of the content of phosphorus and sulfur as the main biogenic elements to the sum of the contents of silicon and aluminum as the main lithogenic elements (respectively, P/(Si+Al), S/(Si+Al)). A metalurgical production site has been localized, which is confirmed by the found bronze products, crucibles and foundry molds. The cultural layer in this location is characterized by an abnormally high sulfur content, which can be attributed to the gypsum entry into the soil, which was used in the creation of molds. According to the results of chemical analyses, the cultural layer of the monument is mainly represented by clay material, which indicates the presence of adobe walls and clay paving of the floor. The clay used in the construction and the clay in the immediate vicinity of the monument are absolutely of the same type, which indicates the use of local raw materials. Sections of the cultural layer with increased enzymatic activity have been identified, which indicates that large volumes of organic material of anthropogenic nature have entered the soil. Such sites presumably correspond to places of accumulation of household garbage, which is confirmed by a high concentration of artifacts and bones.